Chapter Cinesità fluide: avventure di cinesi nel mondo - Pedone, Valentina (Studi di Traduzione Letteraria Lusofona, 2022)
The article by Valentina Pedone focuses on Chinese migration flows to the South-East Asia, offering a wide historical view of those migration flows and a very interesting analysis of the literary works which have been edited by Chinese or Chinese descendants abroad.